A synergistic approach to enhanced oil recovery by combining in-situ surfactant production and wettability alteration in carbonate reservoirs - Kioumars Taheri; Seyed Hamed Hosseini Majd; Behzad Ghanbarian; Sahar Bakhshian; Sajad Safariniya (Scientific Reports)
Abstract A strong alkali was hydrolyzed in the presence of acidic oil to produce an anionic surfactant to prevent the decline in surfactant value. Also, sodium dodecyl sulfate (SDS) was considered the surfactant, and sodium hydroxide and sodium carbonate were the alkalis. We examined the mechanism of interfacial tension reduction with the alkaline-surfactant and wettability changes in three carbonate rocks. Moreover, the effect of alkaline surfactant on reservoir wettability was investigated by quantitative measurement of the static contact angle. Results showed that the wettability of the reservoir rocks changed by adding the concentration of two types of alkaline sodium hydroxide (NaOH) and sodium carbonate (Na2CO3) to the oil rock. In addition, further enhancement of the sodium-carbonate concentration altered the wettability of the reservoir rock to neutral. Increasing the concentration of sodium hydroxide up to 2000 mg/L led to the wettability alteration of the reservoir rock from oil-wet to strong water-wet and, consequently, to the promotion of oil recovery in the reservoir rocks by using the optimal concentration of alkaline surfactant in the core flooding experiments. Through the core flood simulation, the behavior of alkaline-surfactant flooding employing sodium hydroxide and sodium carbonate was predicted following the historical matching of production data.